Search for excited leptons in proton-proton collisions at √s= 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
The ATLAS detector is used to search for excited leptons in the electromagnetic radiative decay channel ℓ*→ ℓγ. Results are presented based on the analysis of pp collisions at a center-of-mass energy of 7 TeV corresponding to an integrated luminosity of 2:05 fb⁻¹ . No evidence for excited leptons is found, and limits are set on the compositeness scale Λ as a function of the excited lepton mass mℓ*. In the special case where Λ = mℓ* excited electron and muon masses below 1.87 TeV and 1.75 TeV are excluded at 95% C.L., respectively.